2017
DOI: 10.1016/j.jvscit.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Severe generalized dermatitis in a nickel-allergic patient with a popliteal artery nitinol stent

Abstract: We present the case of a patient who developed a full-body desquamating macular-papular, pruritic rash after endovascular placement of a popliteal artery nitinol stent for acute limb ischemia. The rash was resistant to high-dose steroid and immunosuppressive treatment and intensive topical treatment. Patch testing revealed nickel allergy. The stented arterial segment was removed, with significant improvement in his symptoms that allowed the cessation of prednisone and topical treatments. The epidemiology, path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Following insertion, the development or aggravation of vesicular hand eczema and dermatitis in the overlying skin have been described . Dermatitis in nickel‐allergic individuals resulting from the use of various surgical utensils and materials has been described . The prostheses used for hip replacement have changed over time.…”
Section: Sources Of Nickel Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Following insertion, the development or aggravation of vesicular hand eczema and dermatitis in the overlying skin have been described . Dermatitis in nickel‐allergic individuals resulting from the use of various surgical utensils and materials has been described . The prostheses used for hip replacement have changed over time.…”
Section: Sources Of Nickel Exposurementioning
confidence: 99%
“…79 Dermatitis in nickel-allergic individuals resulting from the use of various surgical utensils and materials has been described. 84,85 The prostheses used for hip replacement have changed over time. In the 1960s, they were made of metal-on-metal and had high rates of metal release; from the 1970s, metal-on-plastic models were used, which produced fewer wear particles.…”
Section: Surgical Implantsmentioning
confidence: 99%
“…Regarding the method of reconstruction after stent removal, in some case reports, bypass surgery using an autologous vein was performed; however, in our case, direct suturing was possible since the stent could be removed while leaving sufficient vascular wall, and the suturing distance was short [7,8]. In fact, the findings of two-year follow-up computed tomography showed no aneurysm or stenosis after revascularization, direct suturing seemed to be a good reconstruction method without leaving any artifacts for this case.…”
Section: Discussionmentioning
confidence: 79%
“…The gold-standard treatment for contact allergy is removal of the causative material. Guerra and Kirkwood 6 reported that nickel contact allergy led to severe generalized dermatitis after stent placement in the superficial femoral artery, but the symptoms resolved after removal of the stent. However, we could not simply remove the device from our patient because it was used to treat a ruptured aorta, and it involved replacement of the ruptured aorta with a thoracoabdominal aortic clamp because the stent-graft has a suprarenal stent.…”
Section: Discussionmentioning
confidence: 99%